2022
DOI: 10.1097/pra.0000000000000656
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation Mediates the Relationship Between Therapeutic Alliance and Anxiety in Emerging Adults During Inpatient Psychiatric Treatment

Abstract: Emerging adulthood is a critical developmental period characterized by emotional growth and unstructured living. To date, there is little research on emerging adults-defined as those 18 to 25 years old-with serious mental illnesses and even less on emerging adults in psychiatric hospitals. This study analyzed therapeutic alliance with the clinical team and change in anxiety symptoms in emerging adult psychiatric inpatients with the goal of establishing whether emotion regulation could serve as a mediator betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Remaining problems with emotion regulation have been suggested as a risk factor for relapse in depression after treatment (Visted et al, 2018). Shepard et al (2022) found that emotion regulation mediated the relationship between early therapeutic alliance and improvement in anxiety for emerging adult inpatients. In their study, patients with lower scores on working alliance were more likely to experience higher emotion dysregulation, which in turn predicted less change in anxiety.…”
mentioning
confidence: 99%
“…Remaining problems with emotion regulation have been suggested as a risk factor for relapse in depression after treatment (Visted et al, 2018). Shepard et al (2022) found that emotion regulation mediated the relationship between early therapeutic alliance and improvement in anxiety for emerging adult inpatients. In their study, patients with lower scores on working alliance were more likely to experience higher emotion dysregulation, which in turn predicted less change in anxiety.…”
mentioning
confidence: 99%